PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN NARKOBA (STUDI KASUS DI KEPOLISIAN WILAYAH KOTA BESAR SEMARANG) - Sugito, - (Forum Ilmu Sosial, 2008)
Most of drug abuse victims are included in young ages, which are, between 15 to 25 years old, withthe tendency of increasing number of victims from year to year. Therefore, it needs emphatic actions fromthe law enforcing officers, especially police, to execute law enforcement against drug abuse strictly, byutilizing preventive and repressive measures. In law enforcement against drug abuse, there is a supportivefactor in form of the spirit of police to execute law enforcement; meanwhile, the hindering factor is thelack of fund and active public participations to perform drug abuse preventions.Keywords : Law enforcement, drug abuse